h - Fitzgibbon, Andrew; Lazebnik, Svetlana; Perona, Pietro; Sato, Yoichi; Schmid, Cordelia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The seven-volume set comprising LNCS volumes 7572-7578 constitutes the refereed proceedings of the 12th European Conference on Computer Vision, ECCV 2012, held in Florence, Italy, in October 2012. The 408 revised papers presented were carefully reviewed and selected from 1437 submissions. The papers are organized in topical sections on geometry, 2D and 3D shape, 3D reconstruction, visual recognition and classification, visual features and image matching, visual monitoring: action and activities, models, optimisation, learning, visual tracking and image registration, photometry: lighting and colour, and image segmentation.
Poster session -- Geometry: theory and application -- Learning and large-scale recognition -- Detection and attributes -- Actions and activities -- MRFs and early vision -- Geometry and recognition -- Lights, action.-Semantic segmentation.
Keywords: Computer science; Computer software; Computer vision; Computer graphics; Optical pattern recognition; Biometrics; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics; Image Processing and Computer Vision; Pattern Recognition; Biometrics; Computer Graphics; Algorithm Analysis and Problem Complexity